The business environment of Europe : firms, governments, and institutions - Guay, Terrence R., (Cambridge University Press, 2014)
The Business Environment of Europe is the first textbook to provide a complete overview of Europe's business landscape, examining the region's diverse economies and government policies within historical, political, and cultural contexts. This well-researched text examines the European Union and select European nations, and leads students to a full understanding of the structure and dynamics of specific industries, the impact of globalization on European companies, and the future challenges facing the region's business environment. Numerous tables, maps, figures, case studies and chapter-specific bibliographies support students with little background knowledge of the subject, and lead them to total mastery of the material. Ideal for business students seeking background on the historical and cultural foundations of European business, and for international studies students seeking specific information on European governments, policies and economics, this introductory textbook provides a comprehensive and interdisciplinary overview of the subject.